Analysis of Human Resource Readiness in Supporting the Development of Batur Tourism Village, Semarang Regency - Ary Fiyanto; Yolanda Yolanda (PT. Publikasiku Academic Solution, 2026)
This study aims to analyze human resource readiness in supporting the development of Batur Village as a tourism village in Semarang Regency. Human resources are considered a key factor in the success of tourism village development because they determine how local potential is managed and delivered to tourists. This research uses a descriptive qualitative approach. Data were collected through interviews, observations, and documentation. Informants in this study include local communities involved in tourism activities, tourism managers, and village government officials. The results show that human resource readiness in Batur Village is still not optimal. Several weaknesses are found, especially in foreign language skills, tourism knowledge, and destination management abilities. These limitations affect the quality of services provided to tourists and the overall management of tourism activities in the village. The study also finds that human resource readiness is influenced by several factors, such as education level, access to training, and support from the local government. Limited training opportunities and lack of continuous capacity building are key challenges in improving human resource quality. To improve the situation, human resource development needs to be strengthened through structured training programs, mentoring, and cooperation with educational institutions. These efforts are expected to improve community skills and support better tourism management. In conclusion, improving human resource readiness is essential to support the development of Batur Village as a competitive and sustainable tourism village